Perbedaan Estimasi Volume Perdarahan Antara Metode Tes Hemoglobin Dengan Metode Visual Estimasi Pada Ibu Postpartum - Ardi Panggayuh; Jupriyono Jupriyono (coba, 2017)
Error into account bleeding may contribute to an underestimation of the actual postpartum hemorrhage, postpartum hemorrhage late to recognize. This is especially prominent in order to deal with inadequate facilities where deliveries take place at home and the estimated blood loss using equipment that can not be trusted. In the order of these services, blood may be spilled on the floor, bags, and seep into the ground floor. In addition, estimates of maternal postpartum hemorrhage by midwives generally done by visual estimation, although the method is less accurate. In addition, it is often mixed with amniotic fluid and sometimes with urine, making it difficult to visually estimate by less skilled midwife. The purpose of research is to analyze the difference between the volume of bleeding hemoglobin test method with visual estimation. The population is pregnant women who entered the active phase of labor in BPM " Agustin Dwi Wahyuni ", in accordance with the specified inclusion criteria. Samples were taken from the majority population by purposive sampling, totaling 25. The instrument used to measure the hemoglobin level is HB meter "Family Doctor), the value of Hb levels during the first stage inpartu and Hb value after 2 hours post partum in g / dL. To find out the difference in volume between the test methods hemoglon bleeding by visual estimation used parametric statistical tests that the t-test, with significance α 0:05. The results were analyzed by t-test obtained t count 1,215 <t table 2,145, so it concluded that the differences in methods estimate the amount of bleeding did not lead to differences in the average estimate of the amount of bleeding at 2 hours postpartum. Keywords: Hemoglobin Test, Visual Estimation